SPE Asia Pacific Oil and Gas Conference and Exhibition 2011
DOI: 10.2118/142306-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study on Gas Channeling Characteristics and Suppression Methods in CO2 Flooding for Low Permeability Reservoirs

Abstract: This paper shows the close relation between the displacement effects and reservoir properties in CO2 flooding for low permeability reservoirs. Low permeability reservoirs are characterized by tight matrix, strong heterogeneity and developed fractures. With the increase of CO2 injection rate, the CO2 viscous fingering gets worse in low permeability homogeneous reservoirs. While for low permeability heterogeneous reservoirs, the increase in displacement differential pressure contributes to the enhanced oil recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that miscibility has advantages in enhancing oil recovery and controlling CO 2 breakthrough. 62 To investigate the influence of miscibility on large PV CO 2 flooding and storage, we characterized the life cycle miscibility range. In Figure 15, we can observe the changes in miscibility degree, miscibility range, residual oil distribution, and CO 2 storage efficiency throughout the entire development life cycle.…”
Section: Optimal Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that miscibility has advantages in enhancing oil recovery and controlling CO 2 breakthrough. 62 To investigate the influence of miscibility on large PV CO 2 flooding and storage, we characterized the life cycle miscibility range. In Figure 15, we can observe the changes in miscibility degree, miscibility range, residual oil distribution, and CO 2 storage efficiency throughout the entire development life cycle.…”
Section: Optimal Resultsmentioning
confidence: 99%
“…24,25 Nevertheless, there were also problems or challenges in its application. 26 Due to gravity overlap and viscous fingering, CO 2 is highly prone to breakthrough. For example, after a large amount of CO 2 is injected into fractured reservoirs or naturally fractured reservoirs, CO 2 will first flow through high permeability layers or fractures, causing premature gas breakthrough.…”
Section: Introductionmentioning
confidence: 99%
“…An important industrial application of foams is enhanced oil recovery [4,[9][10][11] where foams can be used to increase the amount of crude oil that can be extracted from an oil field. In this process usually, gas flooding is used where CO 2 and/or N 2 are injected into the reservoir [10,11]. The issue that arises is that these gases are normally less viscous, less dense and highly mobile than both crude and water resulting in gas channeling [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In this process usually, gas flooding is used where CO 2 and/or N 2 are injected into the reservoir [10,11]. The issue that arises is that these gases are normally less viscous, less dense and highly mobile than both crude and water resulting in gas channeling [10,11]. This is when the injected gas goes through high permeability layers and fractures in the porous structure inducing poor displacement of the crude oil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation